Recent Advances in 1D Nanomaterial‐Based Bioelectronics for Healthcare Applications. Issue 3 (2nd March 2022) - Song, Sangmin; Kim, Kyung Yeun; Lee, Sun Hee; Kim, Kyun Kyu; Lee, Kyungwoo; Lee, Wonryung; Jeon, Hojeong; Ko, Seung Hwan
Abstract : Bioelectronics Bioelectronics has been developed to acquire knowledge about electrophysiological modulation of in vitro cultured cells, as well as for therapeutic devices which can manage disease through implantation. Along with biocompatibility issues, various 1D nanomaterial‐based bioelectronic applications are discussed in article number 2100111 by Wonryung Lee, Hojeong Jeon, Seung Hwan Ko, and co‐workers.